Kosteneffektivität von Apixaban zur Verhinderung von Schlaganfällen bei Vorhofflimmern in Deutschland - Reimer, Andreas; Schöffski, Oliver (PharmacoEconomics German Research Articles, 2014)
Background and Objective Apixaban was shown to be superior to warfarin and acetylsalicylic acid in preventing stroke in patients with atrial fibrillation and at least one additional risk factor. This study compared the cost effectiveness of apixaban versus warfarin and acetylsalicylic acid in this patient population in Germany. Methods We constructed a lifetime Markov model with 12 health states, based on the results of the Aristotle and Averroes trial, to evaluate the cost effectiveness of apixaban from the social healthcare perspective. Our base-case assumed a cohort of 65-year old patients with a CHADS2 Score of 2.1. We used a 1-month cycle-length. The outcome was measured in quality-adjusted life-years (QALYs), costs and incremental-cost-effectiveness ratios (ICER). The robustness of the model was tested with one and two way sensitivity analyses. A probabilistic sensitivity analysis was also performed. Results Under base case conditions, total costs per patient were € 33,427 and € 33,118 for apixaban and warfarin. Corresponding QALYs were 10.79 and 10.06 in the lifetime Markov model. The ICER was € 423 per QALY. Monte Carlo simulation demonstrated apixaban was cost-effective in 86 % and 100 % of 10,000 iterations at willingness-to-pay thresholds of € 5,000 and € 50,000 per QALY, respectively. Compared to acetylsalicylic acid or the combination of acetylsalicylic acid and clopidogrel apixaban was the economic dominant therapeutic strategy. Conclusion The Markov model strongly suggests that apixaban therapy in the German health care setting is a cost-effective alternative to warfarin and phenprocoumon, respectively.